DEVELOPING ESSAY WRITING TEACHING MATERIALS BASED ON DISCOVERY LEARNING FOR STUDENTS OF THE ENGLISH EDUCATION STUDY PROGRAM FKIP UNSRI - Erlina Erlina; Rita Hayati; Fiftinova Fiftinova (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
Having good teaching materials integrated with good learning model will help students to achieve their highest potential in learning. Discovery learning model is expected to provide the students with the opportunities to improve their learning capacity as they involved in the process of formulating the concept of new learning materials. The purpose of this study was to develop a practical teaching material for essay writing course based on Discovery Learning Model. The teaching materials were developed in accordance with the steps in Discovery Learning Model to help the students involved in the appropriate thinking skills development. This study applied research and development to develop the teaching materials for essay writing course based on the Discovery Learning Model. The study was conducted to the 7th semester students of English Education Study Program Faculty Universitas Sriwijaya. Questionnaires were used to obtained the data related to the validity and the practicality of the teaching materials developed. The results of the questionnaire showed that the workbook developed were in very valid and medium level of validity in terms of the materials and the design. In addition, based on the students’ responses (81.25%) it was found out that the worksheet used was very practical and can be used without revision.